2015
DOI: 10.1155/2015/149509
|View full text |Cite
|
Sign up to set email alerts
|

Stress among Medical Students and Its Association with Substance Use and Academic Performance

Abstract: Background. Chronic stress among medical students affects academic performance of students and leads to depression, substance use, and suicide. There is, however, a shortage of such research evidence in Ethiopia. Objective. We aimed to estimate the prevalence and severity of stress and its association with substance use and academic performance among medical students. Methods. A crosssectional survey was conducted on a sample of 329 medical students at Jimma University. Data were collected using the General He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
139
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(182 citation statements)
references
References 35 publications
25
139
3
15
Order By: Relevance
“…1 Several studies have examined the prevalence of alcohol intake or misuse in medical students. 2,3 One study found that the prevalence of alcohol use among senior medical students in 23 medical schools was 87.5%, 4 in first, second, and third-year medical students it was 91.8%, 5 86.0% 2 and 95.0%, 5 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several studies have examined the prevalence of alcohol intake or misuse in medical students. 2,3 One study found that the prevalence of alcohol use among senior medical students in 23 medical schools was 87.5%, 4 in first, second, and third-year medical students it was 91.8%, 5 86.0% 2 and 95.0%, 5 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies established that chronic and continued exposure to stressful condition leads to emotional, physical and mental disturbance of the students [11,12]. Persistent stress leads to low self-esteem of students, difficulty in handling situations, sleep disorders, decreased attention and abnormal appetite which eventually effects the academic achievement and personal growth of students [13].…”
Section: Introductionmentioning
confidence: 99%
“…11 The other studies done by Chowdhury et al, Panchu et al, Melaku et al all showed a similar result with academic related stressor being the major contributor of stress. 12,22,23 The vastness of the medical syllabus and lack of proper time management lessons for the students are the main reason for academic causes being the major stressor.…”
mentioning
confidence: 99%